Dual-gate MoS2 phototransistor with atomic-layer-deposited HfO2 as top-gate dielectric for ultrahigh photoresponsivity. (4th March 2021) - Li, Xiao-Xi; Chen, Xin-Yu; Chen, Jin-Xin; Zeng, Guang; Li, Yu-Chun; Huang, Wei; Ji, Zhi-Gang; Zhang, David Wei; Lu, Hong-Liang
Abstract: An asymmetric dual-gate (DG) MoS2 field-effect transistor (FET) with ultrahigh electrical performance and optical responsivity using atomic-layer-deposited HfO2 as a top-gate (TG) dielectric was fabricated and investigated. The effective DG modulation of the MoS2 FET exhibited an outstanding electrical performance with a high on/off current ratio of 6 × 10 8 . Furthermore, a large threshold voltage modulation could be obtained from −20.5 to −39.3 V as a function of the TG voltage in a DG MoS2 phototransistor. Meanwhile, the optical properties were systematically explored under a series of gate biases and illuminated optical power under 550 nm laser illumination. An ultrahigh photoresponsivity of 2.04 × 10 5 AW −1 has been demonstrated with the structure of a DG MoS2 phototransistor because the electric field formed by the DG can separate photogenerated electrons and holes efficiently. Thus, the DG design for 2D materials with ultrahigh photoresponsivity provides a promising opportunity for the application of optoelectronic devices.